Der Blütenflor des Halm-Dschungels - Paradies für Musikanten. Behindern Metaphern die rationale Erkenntnis? - Feine, Angelika (Wydawnictwo Naukowe UAM, 1996)
In the following paper the author tries to discuss the problem of metaphors as an occasionally created language unit. In the further part she puts a question of the metaphorical nominational units which are not language anomalies, and are not contradictory to the rational attempts of cognition. They may also play very various roles also in informational texts. In its multifunctional nature they are a means which in the process of text comprehension does not hamper but stimulates processes of cognition.